Critical reception: a comparison between Rokeya and Woolf - Hasan, Md. Mahmudul (2019)
It is true that the volume of Woolf's writing is larger than that of Rokeya's. However, it is also true that the worth of a writer does not solely depend on the volume of their oeuvre. Material context, artistic ability and the forcefulness of arguments, among other things, are also considered when determining a writer's literary value and significance.